INDICATORS OF ADIPOSITY ASSOCIATED WITH LOW BODY ESTEEM IN ADOLESCENTS - Rêgo,Ana Lúcia Viégas (2020)
ABSTRACT Objective: To investigate the association between weight status and anthropometric indicators of adiposity with body esteem. Methods: Cross-sectional study including 305 adolescents from a public school in Rio de Janeiro, Brazil. Data were collected by a self-administered questionnaire and anthropometric measurements. The Body-Esteem Scale for Adolescents and Adults was used to evaluate total body esteem and the “appearance”, “weight”, and “attribution” domains. Body mass index (weight/stature2) was applied to assess weight status and waist circumference, the central body adiposity. The association between indicators of adiposity and body esteem was assessed using Student’s t-test or Mann-Whitney’s test and linear regression models, stratified by sex and age group. Results: Overweight/obesity was observed in 46% of younger adolescents (10 to 13 year-old girls, 10 to 14 year-old boys), 38% of older boys (15 to 18 year old), and 16% of older girls (14 to 18 year old). For both boys and girls in the younger age group, body mass index and waist circumference (as continuous variables) were inversely associated with total body esteem and weight domain. Overweight/obesity was associated with the appearance body esteem domain only among younger male adolescents; no association was found between either the body mass index or waist circumference and the attribution domain. Conclusions: Indicators of adiposity were associated with low body esteem. These findings underscore the fact that considering adolescents’ feelings concerning their body and appearance is important to promote a healthy control of weight.